Temporal analysis of the start at Sierra Nevada`s World Cup 2008 - de la Fuente Caynzos, B.; Martinez Martinez, L.; Ruz Fernández, G.; Arguelles Cienfuegos, J.; Gómez-López, P.; Hernán Rupérez, O. (Archivos de medicina del deporte, 2008)
Skicross will stand as a new Olympic discipline in Vancouver 2010 (Canada). The disciplines`s particularity lays on the simultaneous participation of 4 skiers competing on an uneven track, combining change-directions and jumps, up to the fi nish. Video analysis on different championships and the competition development by itself have proved that, most of times, the fastest 2 skiers in the start are those who get to the next round. In this report, a temporal analysis is carried out over the world`s hihgest-levelled skiers that took part at Sierra Nevada`s World Cup, held in February 2008. A protocol based on one-direction photoelectric cells, placed at 7`5 and 15 meters far from the start gate, along with synchronized frontal and lateral video record, was designed to do the research. The obtained results suggest a signifi cant correlation between the start time (especially on the fi rst 7`5 meters) and the fi nal women rank. The fewer correlation existing in boys would have been caused to the risky way they face jumps, so the theoretical advantages taken in the start go away for being balanced by jump times, whereas women are more conservative in that point.